Penggunaan Ampas Batang Pisang Terhadap Pertumbuhan Ikan Mas di Desa Salutambun Barat Kabupaten Mamasa - Hasria Alang (Biogenesis: Jurnal Ilmiah Biologi, 2013)
The research of the influence of the banana steam residues as pellet for Cyprinus carpio growth has been done at west Salutambun village, Buntu Malangka Districts, Mamasa Counties. The type of this research is experimental study and the aim of this study to see the effect of alternative pellet for Carp (Cyprinus carpio) growth. The research method include the manufacture and testing of alternative pellets for carp (Cyprinus carpio). Alternative pellets consist of banana stem as the main ingredient, a banana peel, fine bran and sweet potato leaves. Everything yielded then mixed with rice water. The pellets are then dried and cured for one night and then milled to from a circle with a small sircle. The data analysis technique used is completely randomized (RAL) is fine that the F value 14,85** is greater than F table α 0,01 with value 13,74 (F hitung > F tabel). Then there is a very significant effect residual use in the manufacture of banana pellets for carp growth at West Salutambun village, Buntu Malangka Districts, Mamasa Counties.Keywords: Cyprinus carpio (carp), growth, pellets